Optimization of Total Polyphenol Content In Herbal Tea Formula Bay Leaves, Cinnamon, and Black Tea - Raharjo, Sentot Joko; Azizah, Devita Nur; Yusuf, Ayu Ristamaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Polyphenols are one of the secondary metabolites found in bay leaves, cinnamon and black tea. This mixture is formulated for therapy, one of which is chronic degenerative diseases, such as hypertension. This research aims to optimize the formulation of bay leaves, cinnamon and black tea on total polyphenol levels. This research method includes: determining the polyphenol content of the three simplices, designing the formulation design, determining the optimization of the total polyphenol content of the 14 formulations and the conformation of the selected formula using Design Expert 13. The results of the research obtained the total polyphenol content of bay leaves (49.36 mg GAE/g), cinnamon (61.36 mg GAE/g), and black tea (61.73 mg GAE/g). Optimization of the highest polyphenol content was 58.419 mg GAE/g. The optimal formula conformation consisted of 1 gram of bay leaves, 8 grams of cinnamon and 1 gram of black tea, resulting in a polyphenol content of 59.63 mg GAE/g. The conclusion of this research is the optimization of the highest polyphenol content of 58.419 mg GAE/g with a formulation composition of Bay Leaves 10%, of Cinnamon 80%, and of Black Tea 10%.